REFLECTION ON ISLAM AS RAHMATAN LIL ‘ALAMIIN IN THE IDEAL OF THE INDONESIAN STATE - Muntoha; Mahrus Ali (RADJA PUBLIKA, 2023)
Until today, there are still factions trying to turn Indonesia into an Islamic state by imposing a caliphate system on how the government is governed has always been one of the issues that has complicated the development of constitutional politics in Indonesia. This article seeks to examine the applicability of the fundamental principles of the Republic of Indonesia, which has adopted the concept of statehood in accordance with Islamic teachings drawn from the Qur'an, the Sunnah, and scholarly Ijtihad. This article reveals that there are five principles of statehood from Islamic teachings that have been adapted and implemented as national ideals and guidelines for the Indonesian nation, including: (i) The principle of state life must be based on common interests and not individuals (deliberation); (ii) the principle of equality before the law; (iii) the principle of self-government; (iv) the principle of accountability for the head of state; and (v) the principle of justice, equity, equality. The Pancasila precepts have been adjusted to include these five concepts. Indonesia is therefore Islamic, reflecting the kindness of Islam via Pancasila as the Basis of the Unitary State of the Republic of Indonesia without becoming an Islamic state.